Methodology of education used in the education of the tennis during the stage of initiation - José Carlos Carreras Duaigües; Javier Giménez Fuentes-Guerra (FEADEF, 2010)
The main objective of this study is to define the methodological model used in the introduction to tennis in Huelva, as well as emphasize teaching resources employed in the teaching of this sport.The method that has been used is video recording 16 sessions initiating to tennis (2 for each of the 8 monitors). Then proceed to analyze the instructor-trainer from the educational point: position on the track, chosen tasks (with or without opposition), material used, adaptation to the level that imparts and kinds of feedbacks.The most outstanding results have been: the predominant position for the teacher is central, he also elects mainly unopposed tasks, few questions are made but there are incentives and positive reinforcement for correction.We also point out the inadequate training of the instructors, most former players without qualification, different styles of teaching tennis in clubs (less pupils and increased importance of the techniques) or municipal schools (more pupils and more games).This research concludes affirming the consolidation of a technical modified model, with better attitude in teachers when correcting and the presence of more games, a little different from what was used to do in the 80's but showing a lack of draught of the constructivist methodology in those who are responsible initiating sports outside the school environment in the province of Huelva.